Mycobacterium tuberculosis Catalase Inhibits the Formation of Mast Cell Extracellular Traps - Campillo-Navarro, Marcia; Leyva-Paredes, Kahiry; Donis-Maturano, Luis; Rodríguez-López, Gloria M.; Soria-Castro, Rodolfo; García-Pérez, Blanca Estela; Puebla-Osorio, Nahum; Ullrich, Stephen E.; Luna-Herrera, Julieta; Flores-Romo, Leopoldo; Sumano-López, Héctor; Pérez-Tapia, Sonia M.; et al. (Frontiers in Immunology, 2018)
Tuberculosis is one of the leading causes of human morbidity and mortality. Mycobacterium tuberculosis (Mtb) employs different strategies to evade and counterattack immune responses persisting for years. Mast cells are crucial during innate immune responses, and help clear infections via inflammation or by direct antibacterial activity through extracellular traps (MCETs). Whether Mtb induce MCETs production is unknown. In this study, we report that viable Mtb did not induce DNA release by mast cells, but heat killed Mtb (HK-Mtb) did. DNA released by mast cells after stimulation with HK-Mtb was complexed with histone and tryptase. MCETs induced with PMA and HK-Mtb were unable to kill live Mtb bacilli. Mast cells stimulated with HK-Mtb induced hydrogen peroxide production, whereas cells stimulated with viable Mtb did not. Moreover, MCETs induction by HK-Mtb was dependent of NADPH oxidase activity, because its blockade resulted in a diminished DNA release by mast cells. Interestingly, catalase deficient Mtb induced a significant production of hydrogen peroxide and DNA release by mast cells, indicating that catalase produced by Mtb prevents MCETs release by degrading hydrogen peroxide. Our findings show a new strategy employed by Mtb to overcome the immune response through inhibiting MCETs formation, which could be relevant during early stages of infection.